2016
DOI: 10.1161/circgenetics.115.001370
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Molecular Autopsy After Exertion-Related Sudden Unexplained Death in the Young

Abstract: Background-Targeted postmortem genetic testing of the 4 major channelopathy-susceptibility genes (KCNQ1, KCNH2, SCN5A, and RYR2) have yielded putative pathogenic mutations in ≤30% of autopsy-negative sudden unexplained death in the young (SUDY) cases with highest yields derived from the subset of exertion-related SUDY. Here, we evaluate the role of whole-exome sequencing in exertion-related SUDY cases. Methods and Results-From 1998 to 2010, 32 cases of exertion-related SUDY were referred by Medical Examiners f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…the results of a molecular diagnosis have clinical value for relatives who may carry the same mutations; some of which are already clinically actionable. 6,12 This review has collated the results from previous molecular autopsy related studies and showed that a median of 4% of previous SIDS cases can potentially be resolved by a molecular autopsy. While this was significantly lower than the yield from older cohorts of SUDY, these results would have been of particular value to the respective family members.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the results of a molecular diagnosis have clinical value for relatives who may carry the same mutations; some of which are already clinically actionable. 6,12 This review has collated the results from previous molecular autopsy related studies and showed that a median of 4% of previous SIDS cases can potentially be resolved by a molecular autopsy. While this was significantly lower than the yield from older cohorts of SUDY, these results would have been of particular value to the respective family members.…”
Section: Discussionmentioning
confidence: 99%
“…5 Molecular autopsies have shown a resolution of up to 44% in previously unexplained cases (cohort aged 1-19 years old), which brings closure to family members, while also making it possible for blood relatives to be tested for these mutations. 6 Various case reports and studies have been published regarding the number of sudden unexpected death cases which have been potentially resolved by a molecular autopsy; 7,8 however, it is currently unclear how many of these cases were infants. Therefore, the aim of this study was to review the literature to assess the percentage of SUDI cases resolved by molecular autopsies.…”
Section: Introductionmentioning
confidence: 99%
“…Channelopathy due to mutations is an important etiology of SCD and post-mortem genetic testing (Anderson et al 2016;Cann et al 2016), molecular screening (Kauferstein et al 2013), and next-generation sequencing (Campuzano et al 2014;Hertz et al 2015;Millet et al 2014). Whole exome sequencing may be a promising, time-and cost-effective technique for discovering the genetic basis of SCD in at-risk families and patients (Bagnall et al 2014;Hajj et al 2014;Narula et al 2015).…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…In their analyses, eight rare variants in six genes were identified in seven cases. More recently, the same authors performed WES in 21 cases in whom no mutation was found during the screening of KCNQ1 , KCNH2 , SCN5A , and RYR2 ( 67 ). Interestingly, three variants ( CALM2 -F90L, CALM2 -N98S and PKP2 -N634fs) were classified as pathogenic according to the quideline recommendations of the American College of Medical Genetics (ACMG) ( 68 ).…”
Section: Next-generation Sequencing Molecular Autopsy Studiesmentioning
confidence: 99%